Direct and Indirect Bonding Techniques: A Systematic Review - Paolo Albertini; Laura Mele; Mario Palone; Francesca Cremonini (Association of Support to Oral Health Research (APESB), 2021)
Objective: To assess the scientific evidence on direct and indirect bonding techniques to analyse the differences related to treatment time, number of appointments and number of bracket detachments. Material and Methods: The MEDLINE and Cochrane Library databases were searched through to March 2021. Reference lists from the retrieved publications were also examined. The following article types that described data on the different types of direct and indirect bonding techniques in orthodontics were included: prospective and retrospective cohort studies, case-control studies and randomized controlled clinical trials (RCCTs). Two review authors independently assessed eligibility, extracted data, and ascertained the quality of the studies. Results: The search strategy initially resulted in 824 articles, and after a careful selection comprising the inclusion criteria, 12 articles were picked for the final review, specifically 2 cohort studies, 4 case-control studies and 6 RCCTs. The methodological quality was low in 4 studies, medium in 2, and high in 6 articles. Conclusion: The evidence currently available suggests that the use of computer-aided bonding is related to a reduction in treatment time and the number of appointments compared to direct and manual indirect bonding. However, the total bonding time for computer-aided bonding technique, including digital bracket placement, was longer than for direct bonding. Further high-quality RCTs on the differences between direct and indirect bonding are necessary to determine more precise data, as well as additional advantages and disadvantages.